Institutional Pressure And Social Entrepreneurship Orientation: Their Impact On The Performance Of Social Enterprises - Yesi Mutia Basri; Taufeni Taufik; Hariadi Yasni; Rosalina Indah Putri (Universitas Muhammadiyah Malang, 2022)
Social enterprises are organizations that have economic and social goals. However, the performance of the social enterprise is still not satisfactory. In this study, the researchers examined one of the social enterprises that is developing in Indonesia, namely Village Owned Enterprises (BUMDes). This study aim to evaluates the effect of institutional pressure and social entrepreneurial orientation on the social performance of the social enterprise. It looks at the impact of social performance on the social enterprise's financial performance. The population in this study is social enterprise BUMDes in Bengkalis Regency with a stratified random sampling technique. Respondents in this study were BUMDes managers. Data collection was carried out by sending questionnaires directly to BUMDes managers. A total of 103 respondents participated in this study. The data that has been analyzed using Warp PLS shows that institutional pressure and social entrepreneurial orientation have a positive effect on social performance, and have an effect on improving financial performance. This research has implications for supporting institutional theory and improving BUMdes performance.